2016
DOI: 10.1051/epjconf/201611920001
|View full text |Cite
|
Sign up to set email alerts
|

TOLNET – A Tropospheric Ozone Lidar Profiling Network for Satellite Continuity and Process Studies

Abstract: Ozone lidars measure continuous, highresolution ozone profiles critical for process studies and for satellite validation in the lower troposphere. However, the effectiveness of lidar validation by using single-station data is limited. Recently, NASA initiated an interagency ozone lidar observation network under the name TOLNet to promote cooperative multiple-station ozone-lidar observations to provide highly timeresolved (few minutes) tropospheric-ozone vertical profiles useful for air-quality studies, model e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Ozone measurements have been mostly limited to Haute Provence, Garmisch-Partenkirchen and Athens. By contrast, the ozone-lidar network TolNET was implemented in North America (Newchurch et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ozone measurements have been mostly limited to Haute Provence, Garmisch-Partenkirchen and Athens. By contrast, the ozone-lidar network TolNET was implemented in North America (Newchurch et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, more and more ozone lidar systems have even been shut down. Opposite to this development, recently a Tropospheric Ozone Lidar Network (TOLNet, https://www-air.larc.nasa.gov/missions/ TOLNet/) with seven lidar stations was established in North America (e.g., Newchurch et al, 2016;Wang et al, 2017;. It is important to note that even vertical profiles from the impressive MOZAIC (Measurements of Ozone and Water Vapor by Airbus In-Service Aircraft) (Marenco et al, 1998) data base are not able to resolve the fine-scale temporal variability of the vertical distribution of trace constituents because of the rather confined time slots for the aircraft departures and arrivals at the individual airports.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also reported on tropospheric O 3 retrievals from the Tropospheric Emission Spectrometer (TES) and Infrared Atmospheric Sounding Interferometer (IASI), both sensors operating in the thermal infrared spectral range (Oetjen et al, 2016, and references therein). However, the recent study by Neu et al (2017) pointed out substantial differences in the tropospheric O 3 columns derived from different satellite instruments by up to 23%. Therefore, adequate means to accurately monitor the tropospheric O 3 columns from groundbased remote sensing techniques are needed for the validation of the satellite products and/or model simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The differential absorption lidar (Browell, ) is the state‐of‐art technology to routinely measure vertical profiles of O 3 in an altitude range up to the tropopause with a high spatial and time resolution. A Tropospheric Ozone Lidar profiling Network (TOLNet) with six stations has been built in the United States in order to generate consistent and long‐term data sets (Newchurch et al, ). However, the wide usage of this technique is also limited by the high costs of the instruments and their operation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its relative high temporal and vertical resolution, the lidar technique is able to provide measurements to close the gap between localized high temporal resolution measurements typically provided by in situ instruments and the coarse-resolution measurements provided by satellites. This not only allows the study of boundary layer processes, but also provides valuable information for satellite validation purposes (Newchurch et al, 2016). While this makes lidar a very useful tool for atmospheric and validation studies, their high complexity typically requires the presence of a trained operator, posing a limitation to operation schedules and time coverage.…”
Section: Introductionmentioning
confidence: 99%